Neuroprotective Effect of Petroleum Ether, Methanolic and Aqueous Extracts of Fruits of Benincasa hispida on Lipofuscinogenesis and Fluorescence Product in Brain of D-galactose Induced Aging Accelerated Mice - Ambikar, Digambar Balkrishna; Mohanta, Guru Prasad (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Aging is one of the major factors of development of neurodegenerative disorder and also involved in gradual learning and memory loss. In recent years discovery of antiaging drugs is one of the important topic of research. Many plant drugs proved to be reliable treatment for aging associated changes. Aim: The present investigation was aimed at determining the neuroprotective effect of petroleum ether (BHP), Methanolic (BHM) and aqueous extract (BHA) obtained from Benincasa hispida by the measurement of fluorescence product and biochemical parameter like lipid peroxidation, catalase activity and glutathione peroxides activity in the brains of D-galactose induced aging accelerated female albino mice. Methods: D-galactose administration is a well-known model to accelerate normal aging. D-galactose (0.5 ml 5%) was administered for 15 days and accumulation of fluorescence product and lipofuscin granule in cerebral cortex was evaluated. Moreover lipid peroxidation activity and the antioxidant enzymes like glutathione peroxides and catalase activity in cerebral cortex were also evaluated. Furthermore brains of mice subjected to histopathology studies for evaluation of lipofuscin granules. Results: Co-treatment of D-galactose with BHP, BIM and BIA (100 mg/kg, po) reduced the fluorescence product accumulated in the cerebral cortex. BIM and BHA was protective against D-galatose-induced accelerated aging by reducing lipid peroxidation and restoring the enzymatic activity of glutathione peroxidase and catalase. Moreover BIM was also showed decreased accumulation of lipofuscin granules. Conclusion: In conclusion, BIM and BIA were found to be an effective neuroprotective reagent which could reverse D-galactose-induced oxidative damage and acceleration of aging.
Keywords: Neuroprotection; Aging accelerattion; Fluorescence product; Lipid peroxidation; Lipofuscin granules; Benincasa hispida